Konten Pemuda Tersesat dan Pengaruhnya terhadap Efektivitas Dakwah Masa Kini - Perdana Putra Pangestu; Muhammad Bachrul Ulum (Medina-te : Jurnal Studi Islam, 2021)
This study examines the Youtube content of "The Lost Youth" which has been busy being discussed since 2020. The content titled da'wah with this unusual method has succeeded in attracting more than 1 million viewers per episode. Researchers are interested in examining the formula used by the content creators, namely the controversial comedian duo: Tretan Muslim and Coki Pardede, as well as the national preacher Husein Ja'far Al-Haddar in the content, as well as how efficient the content is in the da'wah scene of Islam Nusantara. Not only using a comedic style in the delivery of da'wah, this content is also considered as a suitable tool for questions of today's Muslim youth who have high curiosity, but are constrained by norms in their delivery. This study uses a qualitative method with a descriptive approach. The data in this study were obtained from the Youtube content "The Lost Youth" which was uploaded to the Indonesian Funny Council channel, Jeda Nulis, and the Lost Youth. In addition, supporting data were also obtained by researchers from the activity of content initiators' Instagram accounts, both from feeds, stories, and netizen reactions contained in the comments column. From the research carried out, it can be concluded that this content is content that tries to balance the current Islamic da'wah scene which seems rigid and segmented, into a da'wah that is more open, flexible, fun, and can be felt by the wider community.